Alkaloids as Anticancer Agents: A Review of Chinese Patents in Recent 5 Years - Tao, Hongyu; Zuo, Ling; Xu, Huanli; Li, Cong; Qiao, Gan; Guo, Mingyue; Lin, Xiukun (Recent Patents on Anti-Cancer Drug Discovery, 2020)
Background: In recent years, many novel alkaloids with anticancer activity have been found in China, and some of them are promising for developing as anticancer agents. Objective: This review aims to provide a comprehensive overview of the information about alkaloid anticancer agents disclosed in Chinese patents, and discusses their potential to be developed as anticancer drugs used clinically. Methods: Anticancer alkaloids disclosed in Chinese patents in recent 5 years were presented according to their mode of actions. Their study results published on PubMed, and SciDirect databases were presented. Results: More than one hundred anticancer alkaloids were disclosed in Chinese patents and their mode of action referred to arresting cell cycle, inhibiting protein kinases, affecting DNA synthesis and p53 expression, etc. Conclusion: Many newly found alkaloids displayed potent anticancer activity both in vitro and in vivo, and some of the anticancer alkaloids acted as protein kinase inhibitors or CDK inhibitors possess the potential for developing as novel anticancer agents.
Keywords: cell circle arrest